ANALISIS GANGGUAN BAHASA GAGAP (STUTTERING) DALAM FILM “THE KING’S SPEECH”, PENDEKATAN PSYCHOLINGUISTICS - Mutiara Indah Nirmala Dewi; Rajamuli Amanda Putri (UPPM Politeknik TEDC Bandung, 2022)
ABSTRACT The research tittle is Language Disorder (stuttering) in ‘The King’s speech movie: Psycholinguistics approach. This study aims identifying and describing stuttering the king. The objectives of this study identify and describe (1) factors of the stuttering (2) know the possible treatment and (3) type of stuttering. The study was a descriptive qualitative study with the researcher as the main instrument and the data sheets as secondary instrument. The object of this research the stutterer person. The data were utterances in the form of words, phrases, clauses, and sentences of the stutterer containing and reflecting the phenomenon of stuttering. The data were categorized and analyzed based on category in psycholinguistics study. The result of this research shows that there are three types of stuttering used theory from Campbel and Hill like “repetition of word”, and “stopped”. Researcher found that stuttering of King George VI. Keywords: stuttering, speech and language disorder, socio emotional development.